HIV and hepatitis B co-infection - prevalence and clinical spectrum in a rural tertiary care centre of Northern India - Nim, Ranjit Kumar; Verma, Vivek Kumar; Kumar, Manoj; Kela, Dheeraj; Singh, Brijesh; Singh, Neetu; Singh, Anand Kumar; Kumar, Sushil (International Journal of Research in Medical Sciences, 2017)
Background: HBV and HIV are both endemic in India. Currently, it is not well established what proportion of HIV-positive patients harbours HBV infection in India. No study was done to know the epidemiology of HBV HIV Co infection in rural population of Northern India. So, this study was done to explore the impact of HBV in HIV patients. Methods: Prospective cohort study was conducted on HIV-HBV co infected patients who attended the ART Clinic at ART centre, Department of Medicine, UPUMS, Saifai, Etawah, after obtaining informed consent. Results: Out of these 1751 HIV patients 919 were eligible for start on ART and the remaining were treatment naïve patients. Out of these 1751 HIV positive patients 79 patients were HBS Ag positive. Thus, the prevalence of HBV-HIV co infection at our ART centre was found to be around 4.5%. 68 patients were found to be eligible for start of ART drugs. Out of these 68 patients on ART, 46 (67.6%) patients were alive, 9 (13.2%) were transferred out, 5 (7.4%) patients were lost to follow up (LFU) and 8 (11.8%) expired till the end of the study. Conclusions: HBV co infection is common in HIV serology positive and can cause significant morbidity and mortality especially in the presence of other concurrent cause of liver injury. HBV co infection might associate with severe hepatotoxicity during intake of HAART regimen. For these reasons, prevention and treatment of HBV infection is mandatory in HIV serology positive.